Polish Pension Schemes (Economic and Political Thought, 2013)
The article presents the operations of the Polish pension schemes. Themost important ones are the open pension schemes (OFE); they are oneof the key factors of the economic development in Poland. Their role isespecially evident on the capital market. The participation in the schemes isobligatory. Their growing size and massive financial operations cause that thesuccess of privatization of public sector companies, the situation at the stockexchange and the cost of the issue of bonds to a large extend depend on themat present. The role of optional pension schemes has been much lower so far;their importance will definitely rise in the future.